Multiple corticosteroids allergy in a patient with asthma: a case report - Mahadi, Mahrunissa; Wan Ahmad Kammal, Wan Syazween Lyana; Md Nor, Norazirah; Jamil, Adawiyah (Springer, 2020)
Background: Allergy towards systemic corticosteroid is rare. This case report discusses the investigations to confirm diagnosis and alternative treatments. Case presentation: A 51-year-old asthmatic woman developed severe anaphylactic reaction following administration of systemic hydrocortisone. Skin prick, intradermal, and intravenous provocation tests confirmed allergy to triamcinolone, hydrocortisone, and dexamethasone. Skin prick tests (SPTs) were negative to all the aforementioned drugs. Intradermal test (IDT) with triamcinolone 1:10 concentration resulted in a 2-mm wheal associated with rhonchi. IDT with hydrocortisone 1:10 concentration showed an 8-mm wheal with rhonchi. IDTs to dexamethasone and carboxymethylcellulose were negative. Generalized rhonchi were observed with intravenous dexamethasone full concentration challenge. Conclusions: Corticosteroid allergy should be suspected in asthma patients with worsening bronchospasm after its administration. Due to its rarity, such diagnosis can easily be missed, resulting in increased morbidity and mortality in patients.